The Journey of the On-The-Job Trainees on their Knowledge, Attitudes, and Skills Development under the New Normal - Marcelo Caldito Calabit (Researchparks Publishing, 2022)
The study stood all about the journey of the on-the-job trainee under the new normal in relation to the model and module-based training program of the school. It describes the experiences encountered by the trainees in the development of knowledge, skills, and attitudes (KSA) as the course of internship. Structured and semi-structured questionnaires were utilized through interviews, focused-group discussions, and in-depth interviews to allow themes to flow organically rather than merely asking questions from a prepared question list in a precise order. Qualitative-narrative case study methods were used, utilizing inductive coding, in-vivo, categorizing, and theme analysis of the data that was transcribed from the respondents’ responses. Results revealed that, the COVID-19 pandemic has had an impact on the trainees' learning skills, knowledge, and attitudes as well as on their performance, which contradict to high-quality customer service. Yet, individual enhanced performance immediately leads to profit, and a systematic strategy for measuring and evaluating training programs is essential for achieving consistent performance. It is, therefore, a structured program in place of on-the-job training, better strategies to address individual learning impairments to the development of the trainees that contrast with the goal and objectives of the on-the-job training course.